PENGARUH PENAMBAHAN FLY ASH PELEPAH PISANG SEBAGAI PENGGANTI AGREGAT HALUS PADA KUAT TEKAN DAN KERETAKAN BETON NON STRUKTURAL - Nur Indah Mukhoyyaroh (AGREGAT, 2022)
The use of banana fronds as a mixed material for making concrete has a positive impact from an environmental perspective. Banana trees have a high content of vitamins and carbohydrates, so bananas are often consumed and the leaves are also often used. lignin content of 33.51%. Basically all types of banana trees can be used as additional materials that can strengthen or improve the properties of concrete. This study aims to determine the strong reaction and cracking of concrete due to the addition of fly ash from banana leaves. The research method used for testing the material using ASTM C reference and for compressive strength and cracking of concrete the research method using the reference (SNI 03-1974-1990) with a mixture composition of 0%, 7%, 9% and 11%, with a total number of objects. test 24 pieces. The test results of normal concrete produce an average compressive strength of 175.96 kg/cm², concrete with a variation of 7% banana midrib fly ash produces an average compressive strength of 119.65 kg/cm². Concrete with a variation of 9% produces an average compressive strength of 111.65 kg/cm². Concrete with a variation of 11% produces an average compressive strength of 98.83 kg/cm². So the highest compressive strength produces a variation of 7% with a value of 119.65 kg/cm², and the lowest compressive strength produces a variation of 11% with a value of 98.83 kg/cm². It can be concluded that the larger the material, the higher the compressive strength of the concrete. The highest crack value at the age of 14 days was found in the 7% variation with a value of 26 cm, and the lowest was found in the 11% variation with a value of 15.3 cm. Cracks at the age of 28 days produced the highest crack at 7% variation with a value of 24 cm, and the lowest crack at 9% variation with a value of 13.3 cm.